1954
DOI: 10.1172/jci102865
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Pressure in Leukemic and Non-Leukemic Patients

Abstract: It has been a frequent observation that many patients with leukemia and multiple myeloma bleed freely through the marrow needle at the time of bone marrow aspiration although hemorrhagic tendencies may not be present clinically. In addition , throbbing bone pain and bone tenderness are not infrequently observed in these patients (1). Such clinical observations suggest that some degree of pressure elevation may be present in the marrow cavity in these diseases. It was believed of interest to determine the press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
3

Year Published

1954
1954
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 5 publications
0
6
0
3
Order By: Relevance
“…There is considerable evidence indicating that the marrow arteriolar tone is under nervous control [Drinker and Drinker, 1916;Petrakis, 1954;Stein et al, 1958;Herzig and Root, 1959;Brown-Grant and Cumming, 1962] but the general patterns of marrow vascular response are not clear. In the 'high activity' marrow following haemorrhage the marrow sinusoids become considerably dilated [Branemark, 1959] and the intramyeloid pressure has been reported to fall [Herzig and Root, 1959].…”
Section: And B]mentioning
confidence: 99%
See 3 more Smart Citations
“…There is considerable evidence indicating that the marrow arteriolar tone is under nervous control [Drinker and Drinker, 1916;Petrakis, 1954;Stein et al, 1958;Herzig and Root, 1959;Brown-Grant and Cumming, 1962] but the general patterns of marrow vascular response are not clear. In the 'high activity' marrow following haemorrhage the marrow sinusoids become considerably dilated [Branemark, 1959] and the intramyeloid pressure has been reported to fall [Herzig and Root, 1959].…”
Section: And B]mentioning
confidence: 99%
“…In the 'high activity' marrow following haemorrhage the marrow sinusoids become considerably dilated [Branemark, 1959] and the intramyeloid pressure has been reported to fall [Herzig and Root, 1959]. In human leuksemia marrows both the intramyeloid pressure and the blood flow rate may be increased [Petrakis et al, 1953;Petrakis, 1954]. In hypoxia the marrow blood flow has been reported to increase [Cumming, 1962] but the intramyeloid pressure falls [Kalser et al, 1951].…”
Section: And B]mentioning
confidence: 99%
See 2 more Smart Citations
“…A pressure of 310 mmHg above atm corresponds to less than 0.5% of the maximum pressure acting on the head of the femur of an upright 160 lb person, and therefore, would be physiologically relevant as erosion of the trabeculae from leukemic infiltration increases sensitivity to external forces. 1,2 We found that the growth and viability of these cell lines did not change at high pressure ( Figure 1A). Next, we explored the impact of increased pressure on the sensitivity of these cells to three anthracyclines used in the treatment of AML: daunorubicin, idarubicin, and mitoxantrone.…”
mentioning
confidence: 94%